Bioinformatics: A beginners Guide - Jean Michael Claverie (Wiley India, 2003)
This book is dedicated to unspecialized users starting with bioinformatics from scratch, who are familiar with some biology. It explains the important relationship between the biological sciences and information technology, points readers in the direction of the most helpful web resources and freely available tools. Many chapters in the book are devoted to addressing specific and common biological questions, problems, and projects. · getting started in bioinformatics · a survival guide to bioinformatics · becoming a pro in sequence analysis · becoming a specialist: advanced bioinformatics techniques · the part of tens